2017
DOI: 10.1093/gigascience/gix016
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of the wisent (Bison bonasus)

Abstract: The wisent, also known as the European bison, was rescued from extinction approximately 80 years ago through the conservation of 12 individuals. Here, we present the draft genome sequence of a male wisent individual descended from this founding stock. A total of 366 billion base pairs (Gb) of raw reads from whole-genome sequencing of this wisent were generated using the Illumina HiSeq2000 platform. The final genome assembly (2.58 Gb) is composed of 29,074 scaffolds with an N50 of 4.7 Mb. 47.3% of the genome is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 32 publications
(34 reference statements)
8
25
0
Order By: Relevance
“…BUSCO analysis carried out to assess the completeness of our assembly resulted in a BUSCO score of 96.8% (complete = 93.8%, single = 92.4%, duplicated = 1.4%, fragmented = 3.0%, missed = 3.2%, genes = 4,104). These results are comparable with those for the published European bison (wisent) 34 and domestic yak 4 genomes, suggesting our assembly has high quality and is quite complete.…”
Section: Technical Validationsupporting
confidence: 86%
“…BUSCO analysis carried out to assess the completeness of our assembly resulted in a BUSCO score of 96.8% (complete = 93.8%, single = 92.4%, duplicated = 1.4%, fragmented = 3.0%, missed = 3.2%, genes = 4,104). These results are comparable with those for the published European bison (wisent) 34 and domestic yak 4 genomes, suggesting our assembly has high quality and is quite complete.…”
Section: Technical Validationsupporting
confidence: 86%
“…The analyses of the mitogenomes indicate the alternation of two bison populations with mitotypes for which the age of the MRCA can be estimated to 1.55 [1.74-1.37] Mya whereas the age of the MRCA between the Bison bonasus and Bos primigenius mitotypes can be estimated to 1.27 [1.44-1.12] Mya. This is at odds with the distance separating the genome of Bison bonasus from that of Bison bison (0.37%) and of Bos primigenius f. taurus (0.93%) and reveals that the two bison species are closely related and have diverged long after the divergence of bisontine and taurine groups [8]. The analysis of two modern B. bonasus genomes has revealed that the bison and cattle lineages started diverging about 1.7 Mya followed by an extended period of limited gene flow lasting up to about 850 kya [7].…”
Section: Mitogenome Lineages and Nuclear Genomesmentioning
confidence: 94%
“…Finally, comparative analyses of the wisent and American bison genomes revealed the proximity of these two genomes compared to the cattle genome [8]. The percentage of nucleotide differences between the two bison genomes was low, 0.37%, while either of these genomes was equally distant to the cattle genome with 0.93% differences.…”
Section: Comparative Genomic Analyses Of Ancient and Modern Bisonmentioning
confidence: 97%
See 2 more Smart Citations